Novel Resistance Training–Specific Rating of Perceived Exertion Scale Measuring Repetitions in Reserve. Issue 1 (January 2016) - Zourdos, Michael C.; Klemp, Alex; Dolan, Chad; Quiles, Justin M.; Schau, Kyle A.; Jo, Edward; Helms, Eric; Esgro, Ben; Duncan, Scott; Garcia Merino, Sonia; Blanco, Rocky
Abstract : Abstract: Zourdos, MC, Klemp, A, Dolan, C, Quiles, JM, Schau, KA, Jo, E, Helms, E, Esgro, B, Duncan, S, Garcia Merino, S, and Blanco, R. Novel resistance training–specific rating of perceived exertion scale measuring repetitions in reserve. J Strength Cond Res 30(1): 267–275, 2016—The primary aim of this study was to compare rating of perceived exertion (RPE) values measuring repetitions in reserve (RIR) at particular intensities of 1 repetition maximum (RM) in experienced (ES) and novice squatters (NS). Furthermore, this investigation compared average velocity between ES and NS at the same intensities. Twenty-nine individuals (24.0 ± 3.4 years) performed a 1RM squat followed by a single repetition with loads corresponding to 60, 75, and 90% of 1RM and an 8-repetition set at 70% 1RM. Average velocity was recorded at 60, 75, and 90% 1RM and on the first and last repetitions of the 8-repetition set. Subjects reported an RPE value that corresponded to an RIR value (RPE-10 = 0-RIR, RPE-9 = 1-RIR, and so forth). Subjects were assigned to one of the 2 groups: (a) ES ( n = 15, training age: 5.2 ± 3.5 years) and (b) NS ( n = 14, training age: 0.4 ± 0.6 years). The mean of the average velocities for ES was slower ( p ⩽ 0.05) than NS at 100% and 90% 1RM. However, there were no differences ( p > 0.05) between groups at 60, 75%, or for the first and eighth repetitions at 70% 1RM. In addition, ES recorded greater RPE at 1RM than NS ( p = 0.023). In ES, there was a strong inverse relationship between average velocity and RPE at all percentages ( r = −0.88, p < 0.001), and a strong inverse correlation in NS between average velocity and RPE at all intensities ( r = −0.77, p = 0.001). Our findings demonstrate an inverse relationship between average velocity and RPE/RIR. Experienced squatter group exhibited slower average velocity and higher RPE at 1RM than NS, signaling greater efficiency at high intensities. The RIR-based RPE scale is a practical method to regulate daily training load and provide feedback during a 1RM test.